Current Population Survey, November 1979 ([Verlag nicht ermittelbar], 1984)
This data collection supplies standard monthly labor force data for the week prior to the survey. Comprehensive information is given on the employment status, occupation, and industry of persons 14 years old and older. Additional data are available concerning weeks worked and hours per week worked, reason not working full-time, total income and income components, and residence. Besides the CPS core questions, this survey also gathered supplemental data on ethnicity, literacy, and language. Respondents were asked specific questions about their country of birth, parents' countries of birth, citizenship, year of immigration, ancestry, and current language spoken at home. If a foreign language was spoken at home, respondents indicated their ability to read and write this language as well as English. The language spoken at home when the respondent was a child was also identified. In addition, all states and 44 standard metropolitan statistical areas are identified and ranked by population size according to 1970 population figures. Information on demographic characteristics, such as age, sex, race, household relationship, and Hispanic origin, marital status, veteran status, and educational background, is available for each person in the household enumerated.